Effects and safety of auricular acupressure on depression and anxiety in isolated COVID-19 patients: A single-blind randomized controlled trial - Cai, Wa; Zhang, Kun; Wang, Guan-Tao; Li, Jin; Wei, Xiang-Yu; Ma, Wen; Li, Ya-Juan; Wang, Bo; Shen, Wei-Dong (Frontiers in Psychiatry, 2022)
Objective: Psychological distress such as depression and anxiety resulted from coronavirus disease 2019 (COVID-19) have attracted increasing attention. The aim of this randomized controlled trial is to evaluate the effects and safety of auricular acupressure on depression and anxiety in isolated COVID-19 patients. Methods: 68 participants diagnosed with COVID-19 pneumonia (18-80 years old, SDS ≥ 50, SAS ≥ 45) were recruited and randomly allocated to the auricular acupressure group and the sham auricular acupressure group by a computer-generated random number sequence from 9th June to 30th June 2022. The group allocation was only blinded to the participants. Those in the auricular acupressure group were attached magnetic beads against 4 auricular points Shenmen, Subcortex, Liver and Endocrine, while sham group used four irrelevant auricular points. Outcomes were measured by Zung Self-Rating Depression Scale (SDS) and Zung Self-Rating Depression Scale (SAS) before and after treatment in both groups through electronic questionnaire in mobile phones. Results: After treatment, statistically significant differences were found in scores of SAS in both groups (P<0.001 in auricular acupressure group; P=0.003 in sham group), and SDS scores reduced significantly in the auricular acupressure group (P=0.002). Significant reduced SAS and SDS scores were achieved in the auricular acupressure group than that in the sham group (F=4.008, P=0.049, MD -7.70 95% CI: -9.00, -6.40, SMD -2.79 95% CI: -3.47, -2.11 in SDS; F=10.186, P=0.002, MD -14.00 95% CI: -15.47, -12.53, SMD -4.46 95% CI: -5.37, -3.56 in SAS). No adverse events were found in either group during the whole study. Conclusion: Auricular acupressure is an effective and safe treatment for alleviating symptoms of depressive and anxiety in patients with COVID-19.